Intensive and extensive margins of India’s agricultural trade: Implications for export diversification and development - Kannan, Elumalai; Kumar, Anjani (International Food Policy Research Institute, 2022)
This paper analyses relative contribution of intensive and extensive margins to growth in India’s agricultural exports for the period 2001 to 2020. Two alternative approaches are employed to estimating export margins: the traditional approach of using export volume across product lines, and a robust method proposed by Hummels and Klenow (2005). The paper also examines the determinants of export margins through a standard gravity model. Traditional method of decomposing export growth shown that intensification of the export of existing products to existing destinations dominated export growth. The contribution of export diversification to export growth has remained subdued in the last two decades. Within the extensive margin, contribution of product diversification to export growth was more important than the contribution of geographic diversification. According to the Hummels and Klenow approach, during the 2001 to 2020 period, the extensive margin grew at 1.24 percent per annum, while the intensive margin increased at 0.23 percent. The contribution of growth at the extensive margin increased from 58.8 percent in 2001 to 70.2 percent in 2020. Gravity model results revealed that, among other variables, a positive and significant effect of free trade agreement on export margins. Broadly the study results point out that India’s exports along the extensive margin has not been fully exploited and that export diversification holds the key to higher export growth in agricultural products. There is wide scope for expansion of India’s agricultural exports through development of new product varieties and new markets.